2005
DOI: 10.1073/pnas.0505580102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of mRNA transport in the nucleus

Abstract: The mechanism of transport of mRNA-protein (mRNP) complexes from transcription sites to nuclear pores has been the subject of many studies. Using molecular beacons to track single mRNA molecules in living cells, we have characterized the diffusion of mRNP complexes in the nucleus. The mRNP complexes move freely by Brownian diffusion at a rate that assures their dispersion throughout the nucleus before they exit into the cytoplasm, even when the transcription site is located near the nuclear periphery. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
227
3
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(243 citation statements)
references
References 35 publications
(42 reference statements)
10
227
3
1
Order By: Relevance
“…The DNA-oligonucleotide-labeled particles displayed a considerably higher mobility than recorded in previous single-particle experiments (6,7,14). To rule out the possibility that the fast motion was caused by fragmentation of the particles by RNase H, we performed microinjection experiments using fluorescently labeled 2Ј-O-methyl-RNA oligonucleotides complementary to BR2 RNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The DNA-oligonucleotide-labeled particles displayed a considerably higher mobility than recorded in previous single-particle experiments (6,7,14). To rule out the possibility that the fast motion was caused by fragmentation of the particles by RNase H, we performed microinjection experiments using fluorescently labeled 2Ј-O-methyl-RNA oligonucleotides complementary to BR2 RNA.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mobility can be affected by energy depletion, which suggests that ATP-dependent processes also play a role (5). Recently, it became feasible to track individual mRNP particles in the nucleoplasm (6,7). It could then be confirmed that the particles move by free diffusion, but the diffusion is often spatially constrained.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, reductions of this magnitude are not easily explained by rate decreases in enzymatic reactions because, as explained above, one would expect to see a much larger effect upon a 15°C temperature shift (see also Shav-Tal et al, 2004 for a discussion of this point). In addition, a recent study of mRNA movement in the nucleus of mammalian cells has somewhat clarified the situation by revealing that ATP is required for the resumption of movement when RNA becomes corralled within tight confinements, rather than the nucleotide being involved in the movement itself (Vargas et al, 2005). Molenaar et al (2004) also reported that several poly(A) binding proteins moved in and out of speckles at rates similar to those reported here for both bound SC35 and poly(A) RNA, and by others for RNA-binding proteins (Phair and Misteli, 2000;Misteli, 2001;Calapez et al, 2002), but they reported a 5-to 10-fold slower diffusion coefficient for poly(A) RNA itself.…”
Section: Discussionmentioning
confidence: 99%